A contribution to the taxonomy of Centaurea sect. Cynaroides (Asteraceae, Cardueae–Centaureinae) in Iran - Negaresh, Kazem; Rahiminejad, Mohammad Reza (Phytotaxa, 2014)
The taxonomy of Centaurea sect. Cynaroides is revised in Iran. A new species Centaurea karamianiae closely related to C. regia and C. amadanensis is described from Kermanshah Province, W Iran. In addition, C.gabrieliae and C. wendelboi are transferred from C. sect. Cynaroides to the new section C. sect. Ranjbarianae.